The Reliability of the AOSpine Thoracolumbar Classification System in Children: Results of a Multicenter Study. Issue 5 (May 2020) - Mo, Andrew Z.; Miller, Patricia E.; Glotzbecker, Michael P.; Li, Ying; Fletcher, Nicholas D.; Upasani, Vidyadhar V.; Riccio, Anthony I.; Hresko, Michael T.; Krengel, Walter F.; Spence, David; Garg, Sumeet; Hedequist, Daniel J.
Abstract : Background: The purpose of this study was to determine whether the new AOSpine thoracolumbar spine injury classification system is reliable and reproducible when applied to the pediatric population. Methods: Nine POSNA (Pediatric Orthopaedic Society of North America) member surgeons were sent educational videos and schematic papers describing the AOSpine thoracolumbar spine injury classification system. The material also contained magnetic resonance imaging and computed tomography imaging of 25 pediatric patients with thoracolumbar spine injuries organized into cases to review and classify. The evaluators classified injuries into 3 primary categories: A, B, and C. Interobserver reliability was assessed for the initial reading by Fleiss kappa coefficient ( k F ) along with 95% confidence interval (CI). For A and B type injuries, subclassification was conducted including A0 to A4 and B1 to B2 subtypes. Interobserver reliability across subclasses was assessed using Krippendorff alpha (α k ) along with bootstrapped 95% CI. Imaging was reviewed a second time by all evaluators 1 month later. All imaging was blinded and randomized. Intraobserver reproducibility was assessed for the primary classifications using Fleiss kappa and subclassification reproducibility was assessed by Krippendorff alpha (α k ) along with 95% CI. Interpretations for reliability estimates were based on Landis and Koch (1977): 0 to 0.2, slight; 0.2 to 0.4, fair; 0.4 to 0.6, moderate; 0.6 to 0.8, substantial; and >0.8, almost perfect agreement. Results: Twenty-five cases were read for a total of 225 initial and 225 repeated evaluations. Adjusted interobserver reliability was almost perfect ( k F =0.82; CI, 0.77-0.87) across all raters. Subclassification reliability was substantial ( α K =0.79; CI, 0.62-0.90). Adjusted intraobserver reproducibility was almost perfect ( k F =0.81; CI, 0.71-0.90) for both primary classifications and for subclassifications (α k =0.81; CI, 0.73-0.86). Conclusions: The reliability for the AOSpine thoracolumbar spine injury slassification System was high amongst POSNA surgeons when applied to pediatric patients. Given a lack of a uniform classification in the pediatric population, the AOSpine thoracolumbar spine injury classification system has the potential to be used as the first universal spine fracture classification in children. Level of Evidence: Level III.